2018
DOI: 10.1002/ajh.25211
|View full text |Cite
|
Sign up to set email alerts
|

Measurable residual disease, conditioning regimen intensity, and age predict outcome of allogeneic hematopoietic cell transplantation for acute myeloid leukemia in first remission: A registry analysis of 2292 patients by the Acute Leukemia Working Party European Society of Blood and Marrow Transplantation

Abstract: Patients with acute myeloid leukemia (AML) in morphological first complete remission (CR1) pre-allogeneic hematopoietic cell transplantation (HCT) may have measurable residual disease (MRD) by molecular and immunophenotyping criteria. We assessed interactions of MRD status with HCT conditioning regimen intensity in patients aged <50 years (y) or ≥50y. This was a retrospective study by the European Society for Blood and Marrow Transplantation registry. Patients were >18y with AML CR1 MRD NEG/POS and recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 91 publications
5
65
1
1
Order By: Relevance
“…This finding is in accordance with the results of another recent EBMT study of the impact of conditioning with RIC and MAC and MRD status at time of allotransplant in 2292 adult patients with AML in CR1. In this study, MAC and RIC gave similar outcomes except in younger patients (less than 50 years of age) with MRD positive detection, where MAC was associated with lower RI and better outcome . This finding might probably also apply to relapses post ASCT where a positive MRD status in younger patients in CR would favor a MAC regimen.…”
Section: Discussionsupporting
confidence: 65%
“…This finding is in accordance with the results of another recent EBMT study of the impact of conditioning with RIC and MAC and MRD status at time of allotransplant in 2292 adult patients with AML in CR1. In this study, MAC and RIC gave similar outcomes except in younger patients (less than 50 years of age) with MRD positive detection, where MAC was associated with lower RI and better outcome . This finding might probably also apply to relapses post ASCT where a positive MRD status in younger patients in CR would favor a MAC regimen.…”
Section: Discussionsupporting
confidence: 65%
“…These data provide a bona fide preliminary indication that additional pre‐transplant therapy for MRD positive patients may provide clinical benefit and improve post‐transplant outcomes. And, the data complement a recent ALWP/EBMT analysis suggesting superior outcomes for MRD positive patients younger than 50 years of age, with a myeloablative conditioning approach 9 . Alternatively, one may consider that the therapeutic intervention for MRD positive patients should not be in the form of additional therapy, but rather in guided donor selection as suggested by publications demonstrating that choice of alternative donors, namely umbilical cord grafts 30 or haploidentical donors 31,32 may improve on historical results with traditional donors.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, a recently published survey indicates that nearly 70% of leukemia physicians in the US use MRD on a routine basis in the clinic 1 . However, while determination of MRD status provides robust prognostic information in AML patients following induction chemotherapy, consolidation therapy prior to allogeneic stem cell transplantation (allo‐SCT), and post‐transplant, 2‐10 the role positive MRD status should play in clinical decision making remains currently undefined, reflected also in recently published guidelines 11 . Whereas a number of recent studies clearly implicate pretransplant MRD persistency in inferior patient outcome, 12,13 the notion that additional therapy prior to transplant would decrease relapse has not thus far been tested in a scientifically rigorous manner.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of mutated NPM1 as target for minimal residual disease (MRD) has greatly consolidated the armamentarium how best to advise cytogenetically normal AML patients [6]. It was suggested that AML patients <50 years in CR1 with MRD-negativity may have no benefit from allogeneic SCT, whereas patients with MRD-positivity after induction may benefit from myeloablative conditioning [7]. At our center, we consistently consolidate NPM1mut/FLT3wild-type patients with autologous SCT, but also NPM1mut/FLT3-ITD-positive patients in the absence of an available donor or according to patient preference [4,[8][9][10].…”
Section: Lettermentioning
confidence: 99%